Functional State of Myocardium After Combined Application of Therapeutic Hypothermia and Mesenchymal Stromal Cells at Experimental Myocardial Infarction - Trofimova, Anna V.; Chizh, Nikolay A.; Belochkina, Irina V.; Manchenko, Anna A.; Shabliy, Vladimir A.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2015)
N/A